1992
DOI: 10.1021/jm00100a029
|View full text |Cite
|
Sign up to set email alerts
|

L-Thymidine is phosphorylated by herpes simplex virus type 1 thymidine kinase and inhibits viral growth

Abstract: We have demonstrated that herpes simplex 1 (HSV1) thymidine kinase (TK) shows no stereospecificity for D- and L-beta-nucleosides. In vitro, L enantiomers are not recognized by human TK, but function as specific substrates for the viral enzyme in the order: L-thymidine (L-T) >> 2'-deoxy-L-guanosine (L-dG) > 2'-deoxy-L-uridine (L-dU) > 2'-deoxy-L-cytidine (L-dC) > 2'-deoxy- L-adenosine (L-dA). HSV1 TK phosphorylates both thymidine enantiomers to their corresponding monophosphates with identical efficiency and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 1 publication
3
64
0
Order By: Relevance
“…To this purpose, chemical modifications of the sugar ring, such as replacement of the 4h-oxygen by a methylene group [1,2] or replacement of the -2h-deoxyribose or the carbocyclic -2h-deoxyribose by their respective  enantiomers [3][4][5] have indeed given rise to nucleosides resistant to such degradation and which remain active as anticancer and antiviral agents [17]. Replacement of the 4h-oxygen by sulphur was also studied, but only in the case of ribonucleosides [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To this purpose, chemical modifications of the sugar ring, such as replacement of the 4h-oxygen by a methylene group [1,2] or replacement of the -2h-deoxyribose or the carbocyclic -2h-deoxyribose by their respective  enantiomers [3][4][5] have indeed given rise to nucleosides resistant to such degradation and which remain active as anticancer and antiviral agents [17]. Replacement of the 4h-oxygen by sulphur was also studied, but only in the case of ribonucleosides [18].…”
Section: Discussionmentioning
confidence: 99%
“…HeLa TK − cells (human epithelial cell line derived from a cervix carcinoma, TK-deficient) and HeLa TK − \HSV-1 TK + (HeLa TK − transformed to the TK + phenotype with a functional copy of the HSV-1 TK gene) were those previously used [3]. Cells were tested for mycoplasma contamination with the Hoechst 33258 staining method and were found to be negative.…”
Section: Cells and Virus Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the lack of enantioselectivity of HSV-TK in comparison with mammalian TK, 14 we used L-thymidine (LT), the enantiomer of the naturally occurring D-thymidine, in order to trace HSV-TK-containing cells without interfering with cell metabolism and survival ( Figure 1). LT is considered very safe, and neither in vitro nor in vivo studies have shown any sign of cellular or mitochondrial toxicity.…”
Section: Introductionmentioning
confidence: 99%